1993
DOI: 10.1021/bi00091a023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the palmitoylation and membrane targeting domain of neuromodulin (GAP-43) by site-specific mutagenesis

Abstract: Neuromodulin (GAP-43) is a neurospecific calmodulin binding protein which is implicated in neuronal growth and regeneration. It is concentrated in neuronal growth cones and associates with membranes through the palmitoylation of the N-terminal peptide MLCCMRRTK at Cys-3 and Cys-4. In the present study, we have identified critical amino acid residues required for palmitoylation and membrane association of neuromodulin in vivo. Several neuromodulin constructs with point mutations were tested for membrane associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 43 publications
6
52
0
Order By: Relevance
“…Mutation of Cys-3 and Cys-4 blocks radiolabel incorporation, suggesting that these residues are the sites of modification (27). To study the nature of thioester-linked palmitoylation on a molecular level, we attempted to isolate the N-terminal palmitoylated peptide of GAP-43.…”
Section: Analysis Of Tryptic Digests Of Gap-43-gap-43 Has Beenmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutation of Cys-3 and Cys-4 blocks radiolabel incorporation, suggesting that these residues are the sites of modification (27). To study the nature of thioester-linked palmitoylation on a molecular level, we attempted to isolate the N-terminal palmitoylated peptide of GAP-43.…”
Section: Analysis Of Tryptic Digests Of Gap-43-gap-43 Has Beenmentioning
confidence: 99%
“…A previous study showed that the L3 mutant of GAP-43, in which Cys-3 is substituted with Leu, incorporates [ 3 H]palmitate to 75% of the level of the wild type protein (27). When the L3GAP-43 expressed in COS-1 cells was purified, digested with Tev protease, and analyzed by mass spectrometry, a peptide of monoisotopic m/z ϭ 2815.93 was observed, consistent with an acetylated but not palmitoylated N terminus.…”
Section: Analysis Of Tryptic Digests Of Gap-43-gap-43 Has Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…The first 35 amino acids of SCG-10, which include the palmitoylated cysteines at positions 22 and 24, contain the membrane-targeting information (16). Membrane association of GAP-43 is dependent upon palmitoylated cysteines at positions 3 and 4 (17). Previous studies have demonstrated that the palmitoylated cysteines are necessary for membrane association of SNAP-25 (18,19).…”
mentioning
confidence: 98%
“…B-50/GAP-43 is conveyed by fast anterograde axonal transportS,6,27,31,48,49,54 attached to vesicles by palmitoylation of its N-terminal domain. 36,47 In the rat sciatic nerve, B-50/GAP-4335'54 and synaptophysin ~3 are also translocated retrogradely.…”
mentioning
confidence: 99%